HUBUNGAN KONSEP DIRI DENGAN DEPRESI POSTPARTUM DI RUMAH SAKIT UMUM SEMBIRING DELI TUA TAHUN 2018 - Evalina Manurung (Fakultas Kebidanan Institut Kesehatan Deli Husada, 2019)
In Indonesia it was originally estimated that the incidence rate was lower or lower than other countries or communities in other countries. The purpose of this study was to analyze the relationship of self-concept to postpartum depression in RSU Sembiring Deli Tua in 2018.The type of research used was analytical with cross-sectional approach. The nonprobability sampling technique with consecutive sampling with a population of mothers giving birth in 2017 was 759 people. The statistical test results that using the Chi-Square test obtained there was a significant effect between Self-image / body image and postpartum depression, there was a significant effect between Ideal Self and the incidence of postpartum depression, there is a significant effect between Self-Esteem and postpartum depression, there is a significant effect between Self Identity and postpartum depression Probability. It is expected that health workers to inform closestpeople to postpartum mothers, and also it is expected to provide support to mothers that make mothers feel acceptance of themselves, and postpartum mothers feel the guarantee of safety and protection and confidence.